Penguatan kapasitas masyarakat dan pembentukan POKDARWIS dalam pengembangan Desa Wisata Bukek berbasis community-based tourism - Yudi Heryadi; Fajar Surahman; Fadali Rahman; Muhammad Zarmuji; Fahad Assaudi (Penamas: Journal of Community Service, 2026)
Developing a tourism village based on the Community-Based Tourism (CBT) model requires active community participation, positioning the community as the primary actor in the sustainable management of tourism assets. This community service initiative aimed to enhance community capacity and establish a Tourism Awareness Group (POKDARWIS), a local institution capable of independently managing Bukek Tourism Village. Implementation methods included disseminating the CBT concept, providing training on institutional management and human resource capacity building, offering guidance on developing work programs, and facilitating the formation of the POKDARWIS organizational structure. Evaluation was conducted through observation, discussions, and a comparison of participants' understanding levels before and after the activities. The results demonstrated an improved community understanding of tourism village management, the successful establishment of POKDARWIS and its organizational structure, and the formulation of an initial work plan to guide the destination's development. The community also showed an increased commitment to collaborative participation in managing tourism assets.